Orthodontics principles and practice - Gill, Daljit S.; Naini, Farhad B.; ebrary, Inc. (Chichester, West Sussex : Wiley-Blackwell, 2011)
"Orthodontics: Principles and Practice is the latest in the Dental Update books series, offering a clear and comprehensive guide to contemporary orthodontic practice. Offering a highly practical clinical manual format, it covers patient assessment, diagnosis and treatment planning of both standard class malocclusions and specific entities (such as impacted teeth, digit sucking habits and asymmetries) appliance techniques, complex and multidisciplinary care, and retention"--Provided by publisher.
Machine generated contents note: Section 1: Growth & Development.Facial Growth & Development of Dental Occlusion (New). Section 2: Clinical Patient Assessment.Orthodontic Records -. Photography; (New).Radiography (OPG; Lat Ceph & basic analysis) (New).Study Models - Space Analysis - mixed dentition and adult (New).Facial aesthetics (New).Smile Aesthetics.Psychology of facial appearance.Index of Orthodontic Treatment Need (IOTN).Timing of orthodontic treatment.Medical Conditions of relevance to Orthodontics (New).Consent (New).Oral Hygiene techniques in orthodontics (New).Iatrogenic Damage and Orthodontics.Section 3: Diagnosis & Treatment Planning.Class I - (New).Class II - Treatment Planning in Class II Malocclusion (New).Class III - Treatment Planning in Class III Malocclusion.Section 4: Diagnosis, Treatment Planning and Management of specific entities.Digit-sucking habits (New).Impacted incisors.Impacted canines.The management of transverse maxillary deficiency.Poor prognosis first permanent molars.The management of deep overbite.The management of anterior open bite.Orthodontic implication of traumatized maxillary incisors.The diagnosis and management of supernumerary teeth (New).Infraocclusion.Asymmetries (New).Sleep apnoea.Section 5: Appliance Techniques .The straight wire appliance (New).Self-ligating bracket systems (New).Aesthetic Appliances (New).Scientific Evidence for Pre-adjusted Edgewise Mechanics.Bonding/debonding techniques (New).Functional appliances.The Twin block appliance.The Early Management of Class III Malocclusions using Protraction Headgear.The Contemporary Use of Removable Orthodontic Appliances.Section 6: Complex & Multidisciplinary care.Hypodontia (New).The management of missing lateral incisors.The management of missing second premolars.The Periodontal-orthodontic interface.Implants for anchorage.Orthognathic surgery (New).Management of cleft lip and palate (New).Distraction osteogenesis (New).Section 7: Retention.Retention.Late Lower Arch Crowding: The Aetiology Reviewed.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Orthodontics; Electronic books